A Case of Blunt Trauma of the Eyeball Associated With an Inferior Oblique Muscle and an Inferior Rectus Muscle Rupture. Issue 5 (September 2016) - Nitta, Keisuke; Kashima, Tomoyuki; Miura, Fumihide; Hiroe, Takashi; Akiyama, Hideo; Kishi, Shoji
Abstract : Rupture of the extraocular muscle in the absence of significant injury to the eyeball and adnexa is uncommon. The authors report a case of blunt trauma of the eyeball associated with an inferior oblique muscle and an inferior rectus muscle rupture. A 55-year-old man slipped and fell down hitting his eye on an extended windshield wiper blade. Although he had treatment in the emergency room, he complained of diplopia in the primary position 1 day postoperatively. After noticing ruptures of the inferior oblique muscle and an inferior rectus muscle during exploratory surgery, the authors carefully repaired it. Diplopia in the primary position had disappeared within 1 month after the operation and by 6 months postoperatively. The movement of the eye had almost completely recovered. Abstract : This is a rare case of a blunt trauma of the eyeball associated with the rupture of extraocular muscles without extensive damage to the eyeball.